Counting, Carrying, Crafting: Mapping Citations Otherwise - Oostindie, Maud; Spronck, Veerle (KULA, 2026)
This multimedia exchange explores the politics of citation beyond traditional academic formats, engaging with issues of citational justice through text, drawings, collages, maps, and knitted data visualisations. Through an email correspondence, we reflect on the tensions between quantification and the lived, relational nature of scholarly influence. While citation counts and diversity metrics can reveal biases, they also risk abstracting knowledge into numbers. This article asks what it means to do justice to the people, ideas, and experiences that shape academic work.Turning to alternative metaphors—carrying and mapping—we reconsider citation as an embodied and material practice. Carrying evokes the ways knowledge is gathered, held, and moved with over time, while mapping traces connections, highlights omissions, and navigates shifting terrains of influence. These approaches make space for sources that may not fit conventional reference lists: fleeting conversations, students’ insights, artistic works, or moments of observation.Through text, image, and craft, we explore a citational practice that embraces complexity and multiplicity. Ultimately, we propose an expanded citational practice that acknowledges a wider range of influences and explores how other formats might better accommodate these forms of knowledge. The exchange results in a “reference map” in which we experiment with an alternative strategy for citation.